Hak Asuh Anak Pasca Perceraian dalam Perspektif Hukum Islam dan Hukum Positif Indonesia - Masyhadi, Ahmad; Mahmudi, Muhammad Aly (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2024)
Divorce can have a profound impact on the psychology of children, who may feel confusion and uncertainty regarding their family roles and identity. Therefore, in every divorce process, determining child custody is very important to ensure that the child continues to receive attention. Formulation of the problem of this research, What are the provisions for post-divorce child custody according to Islamic law and Indonesian positive law, as well as what are the similarities and differences between the two and what factors are considered by Islamic law and Indonesian positive law in determining post-divorce child custody divorce. This research aims to discuss post-divorce child custody rights from two legal perspectives, namely Islamic law and Indonesian law, as well as explaining the differences and similarities between the two. In addition, this research discusses the factors considered by Islamic law and Indonesian positive law in determining child custody after divorce and how they are implemented in judicial practice in Indonesia. The research approach used is a comparative approach. This research analyzes the differences and similarities in post-divorce child custody rules. Islamic law and Indonesian law have similarities in basic principles, namely the best interests of the child. Both also consider the child's age, the parents' abilities, and the child's welfare as the main factors in determining child custody. However, there are significant differences in legal sources, approaches to the age of the child, the role of the courts, and the influence of religion in determining custody.